Low Diastolic Blood Pressure Predicts Good Clinical Outcome in Patients With Cerebral Venous Thrombosis - Li, Min; Pan, Liqun; Gao, Xiaogang; Hou, Jiaojiao; Meng, Ran; Ji, Xunming (Frontiers in Neurology, 2021)
Background: Cerebral venous thrombosis (CVT) refers to a stroke subtype characterized by the disturbance of cerebral venous outflow caused by venous thrombosis. Previous studies have reported a range of factors that predicts the prognosis of CVT. This study is aimed to find out whether systolic blood pressure (SBP) and diastolic blood pressure (DBP) are suitable as potential indicators of the severity and clinical outcome in CVT patients. Methods: The CVT patients admitted to Xuanwu Hospital from January 2014 to December 2019 were enrolled. The severity of CVT was assessed by the National Institute of Health Stroke Scale (NIHSS) and intracranial pressure (ICP) at the time of admission. Modified Rankin Score (mRS) was assessed at 6 months of follow-up. Results: 156 CVT patients were enrolled with a mean age of 35.8±12.8 years. 55.8% of the CVT patients recruited were female and 17.3% were either pregnant or in perinatal period. Headache was the most common symptom. SBP and DBP were not correlated with NIHSS at admission. Furthermore, SBP and DBP had no impact on the disturbance of consciousness, epilepsy, intracranial hemorrhage and mental disorders. However, SBP and DBP were positively correlated with ICP at admission. SBP > 129.5mmHg and/or DBP > 77.5mmHg suggested the presence of intracranial hypertension (IH). Based on current results, SBP was not correlated with mRS at 6 months of follow-up. However, DBP was found to be positively correlated with mRS at 6 months of follow-up. DBP in CVT patients with good prognosis was significantly lower than in those with poor prognosis. DBP > 79.5 mmHg was identified as a cutoff value to predict a poor clinical outcome. A higher mRS and a higher rate of poor clinical outcome were found in CVT patients with SBP > 146 mmHg or DBP > 79.5 mmHg compared to those with SBP ≤ 146 mmHg or DBP ≤ 79.5 mmHg. Conclusion: SBP > 129.5mmHg and DBP > 77.5mmHg suggested the presence of IH in CVT patients. DBP > 79.5 mmHg predicted a poor clinical outcome.